2015
DOI: 10.1039/c5ob01652e
|View full text |Cite
|
Sign up to set email alerts
|

Helical peptaibol mimics are better ionophores when racemic than when enantiopure

Abstract: Helical peptide foldamers rich in α-aminoisobutyric acid (Aib) act as peptaibol-mimicking ionophores in the phospholipid bilayers of artificial vesicles. Racemic samples of these foldamers are more active than their enantiopure counterparts, which was attributed to differing propensities to form aggregates with crystal-like features in the bilayer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 46 publications
1
21
0
Order By: Relevance
“…Peptides 1 to 9 were synthesized according to previously published procedures . All samples were re‐purified by high‐performance liquid chromatography (HPLC) on an Agilent (Santa Clara, California, United States) 1100 series HPLC equipped with a semi‐preparative C‐18 column (Agilent Eclipse XDB‐C18, 5 μm, 9.4 mm×250 mm).…”
Section: Methodssupporting
confidence: 83%
See 2 more Smart Citations
“…Peptides 1 to 9 were synthesized according to previously published procedures . All samples were re‐purified by high‐performance liquid chromatography (HPLC) on an Agilent (Santa Clara, California, United States) 1100 series HPLC equipped with a semi‐preparative C‐18 column (Agilent Eclipse XDB‐C18, 5 μm, 9.4 mm×250 mm).…”
Section: Methodssupporting
confidence: 83%
“…Like the naturally occurring peptaibols, foldamers 1 to 9 have both N‐ and C‐ termini functionalized. These caps can modulate the stability of the 3 10 ‐helix, for example, a t Bu ester induces formation of a destabilizing Schellman‐like motif at the C‐terminus of the peptides, whilst an N‐terminal Cbz (PhCH 2 OC(O)) adds an extra hydrogen bond that can stabilize the 3 10 ‐helix . Nonetheless, Aib foldamers with four residues or more form 3 10 ‐helical structures even in the presence of destabilizing capping groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aib foldamers that were too short to span the membrane were much less active. They may act through an “amyloid-like” mechanism that has been suggested for other short Aib foldamers, 57 where at high concentrations the foldamers assemble in or around the membrane surface, porating and weakening the bilayer. The longer foldamers were remarkably effective ionophores.…”
Section: Discussionmentioning
confidence: 99%
“…We have observed membrane activity for Aib foldamers containing as few as 5 residues, but studies on the N 3 Aib n C(O)OCH 2 CH 2 SiMe 3 compound family ( n =4 to 13) showed a strong increase in activity when n ≥9 (Figure c) . Planar bilayer conductance (PBC) studies showed clear channel‐like behaviour for n =11 and 13, but not for n =7 and 8 .…”
Section: Resultsmentioning
confidence: 99%